Pengaruh Budaya Kolaboratif Dan Lingkungan Kerja Yang Kondusif Terhadap Kinerja Karyawan IT Di Organisasi BRIN - Muhammad Thoriq Fadhlurrohman; Zia Wardhany (Asosiasi Riset Ilmu Manajemen Kewirausahaan dan Bisnis Indonesia, 2024)
This research focuses on investigating how collaborative culture and work environment affect employee performance at BRIN Organization, particularly in the IT division. Using a qualitative approach, this research combines in-depth observations and interviews with IT employees to comprehensively understand the dynamics of work culture and the physical environment in which they work. The results confirmed that a collaborative culture, characterized by open communication, trust, and a focus on shared goals, plays a major role in improving IT employee performance. Findings show that when teams feel supported and empowered to collaborate, they tend to be more productive and efficient in carrying out their tasks. However, the work environment also plays an important role in supporting employee performance. While there are still some challenges such as lighting issues, a conducive work environment, with a comfortable atmosphere and minimal distractions, has been shown to contribute to employee comfort and focus as well as performance. This suggests that investing in improvements to the physical environment of the office can have a significant positive impact on the well-being and performance of IT employees there. Overall, the results of this study highlight the importance of a collaborative work culture and a conducive work environment in creating favorable conditions for employees to achieve optimal performance. By reinforcing a positive work culture and improving aspects of a supportive work environment, the BRIN Organization can create a work environment that allows employees to thrive and contribute to their full potential.